The Mechanisms of High N2O Emissions from Greenhouse Vegetable Field Soils. Issue 10 (14th September 2017) - Wang, Jing; Zhang, Jinbo; Müller, Christoph; Cai, Zucong
Abstract : Vegetable cultivation in China is characterized by high N application rate, multiple cropping, and frequent irrigation, which may have caused high N2 O emission. However, the N2 O emission characteristics and the underlying mechanisms responsible for N2 O emission under high N application rate in the greenhouse vegetable field soils remains largely unknown. Thus, we conducted a field experiment to monitor N2 O emissions using static chamber and gas chromatography techniques. Meanwhile, an incubation experiment was carried out to quantify soil gross N transformation rates and N2 O emissions pathways via 15 N tracing and N2 O source partitioning methods, respectively. The experiment involved three treatments: Conventional farmland cultivated with soybean (CF), greenhouse vegetable field receiving only chemical N fertilizer (CGV), and greenhouse vegetable field receiving both organic manure and chemical N fertilizer (OGV). Our results showed that soil N2 O emissions in the greenhouse vegetable fields, especially in OGV treatment, were significantly higher than those in CF treatment. Heterotrophic nitrification was the dominant pathway for N2 O emissions accounting for up to 84.0% of the total N2 O flux. The gross heterotrophic nitrification rate was 19.52 mg N kg −1 per day (accounting for 81% of the total nitrification rate) in OGV treatment, which was significantly higher than in CGV and CF treatment. As a consequence, the application of nitrification inhibitors might not be an effective mitigation options of N2 O emissions from the greenhouse vegetable fields in China. Abstract : The contribution of heterotrophic nitrification to N2 O emissions and N2 O production rates due to heterotrophic nitrification increase significantly with increasing gross heterotrophic nitrification rates. This shows that the application of nitrification inhibitors might not be an effective option to mitigate N2 O emission from the greenhouse vegetable fields in China.